Rural Education Enhancement Strategies: Bridging the Urban-Rural Education Gap - Mohd. Shafi Bhat (RADJA PUBLIKA, 2023)
In many regions worldwide, rural communities continue to face educational disparities when compared to their urban counterparts. This article investigates the critical issue of rural education enhancement with a focus on narrowing the urban-rural education gap. The objectives involve conducting a comprehensive assessment of the current state of rural education, shedding light on existing challenges and disparities in terms of infrastructure, resources, and educational outcomes. Next, the article explores successful strategies and best practices that have been employed to enhance rural education. This includes an examination of innovative teaching methodologies, technology integration, community engagement, and teacher training initiatives. Furthermore, the study evaluates the impact of these enhancement initiatives, emphasizing improvements in student learning outcomes, school attendance, retention rates, and overall educational attainment in rural communities. Evidence-based recommendations are offered for policymakers, educators, and community stakeholders to facilitate equitable access to quality education in rural areas. By addressing these objectives, this article aims to contribute to the ongoing efforts to bridge the urban-rural education gap and empower rural communities through enhanced educational opportunities.